2020
DOI: 10.21203/rs.2.18245/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of a health education intervention on the use of long-lasting insecticidal nets for the prevention of malaria in pregnant women of Pakistan: a quasi-experimental study

Abstract: Abstract Background About one quarter of pregnant women in the population of Pakistan are using long-lasting insecticide-treated bed nets (LLINs) for prevention of malaria. Past research reported that adequate information and education would act as mediator to change behaviour among patients for prevention of malaria infection. The effective use of LLINs would contribute to reduction of disease burden caused by malaria. The aim of this study was t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, prior to this intervention, participants had limited knowledge about diabetes, which statistically improved after giving the health education sessions at their work place. These findings were supported by the interventional studies conducted in similar settings, where it has been proved that the health education can change individual's knowledge and behaviours to prevent certain diseases and infections [1,18,21,22]. Moreover, literature has also revealed the similar findings that the health literacy is an important strategy used for the better prevention against non-communicable diseases in the community [6,7,[11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 59%
“…However, prior to this intervention, participants had limited knowledge about diabetes, which statistically improved after giving the health education sessions at their work place. These findings were supported by the interventional studies conducted in similar settings, where it has been proved that the health education can change individual's knowledge and behaviours to prevent certain diseases and infections [1,18,21,22]. Moreover, literature has also revealed the similar findings that the health literacy is an important strategy used for the better prevention against non-communicable diseases in the community [6,7,[11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 59%
“…Another important finding of this study was an increase in the use of LLINs following malaria preventive education. Similarly, there are studies that have shown increase in the use of LLINs when respondents received educational activity ( Kumar et al, 2020 ; Ahmadi et al, 2012 ; Envuladu et al, 2012 ). Some factors that affect LLINs utilization in pregnancies include educational status, age groups, employment status and income level ( Nkoka et al, 2018 ).…”
Section: Discussionmentioning
confidence: 93%
“…It is noteworthy that education intervention had been observed by various studies as a valuable tool in malaria prevention and control in SSA ( Protopopoff et al, 2007 ). Results of a recent study done by Kumar et al in Pakistan suggested that educational intervention is an effective means of improving malaria knowledge and LLINs use among pregnant women ( Kumar et al, 2020 ). Similarly, a study done among nursing mothers by Amoran in Ogun state, south-west, Nigeria showed that education intervention remain effective in influencing behaviour change and improving knowledge of malaria and benefits of LLIN use ( Amoran, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…They have a higher chance to be bitten by a mosquito, especially for those who work in forestry, agriculture, or social services, as well as in plantations or agriculture resulting in a higher occurrence of malaria [27,28]. Other risks may arise from the improper use of insecticide-treated nets or long-lasting insecticidal nets [29][30][31]. Defensive strategies or exposure to malaria prevention techniques used in national malaria control initiatives at the household level may have an impact on lowering the occurrence of malaria [12].…”
Section: Discussionmentioning
confidence: 99%